RAMALAN PRODUKSI KURSI SOFA PADA MEBEL ERLAN HATIVE BESAR DI KOTA AMBON - Aprilian Tampi; Febiola Matuankotta; Grace Fredriksz (P3M Politeknik Negeri Ambon, 2023)
The purpose of this study is to calculate and analyze the production forecast for sofa chairs at Erlan Furniture for the next 3 year period from 2022-2024. Mebel Erlan is a company furniture sector, that manufacture and sale of sofa chairs according to consumer demand based on the order data obtained. The production of sofa chairs is always increasing in every year. In this study used Linear Trend Analysis with the Least Squares Method using the equation Y = a + bx and to determine the accuracy of known forecasts used Standard Error of Estimate Analysis. From the results of the forecasting analysis it is expected that Erlan Furniture can be used as an input in developing company activities, especially in knowing the number of products that must be produced. The results of the calculated of the Linear Trend Analysis can be seen that the forecast for sofa chair production at Erlan Furniture is that in 2022 there will be 113 Sofa Chair Units, in 2023 there will be 114 sofa chairs, and in 2024 there will be 115 sofa chairs. Standard Error of Estimate Analysis Calculation, shows that the level of error from the results of production forecasting calculations is 14 sofa chairs. These figures can be a reference for Erlan Furniture to plan the number of products that must be produced to fulfill consumer needs. Keyword: Forcasting Production Â